2015
DOI: 10.1371/journal.pone.0131820
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oxytocin Receptor Gene (OXTR) rs53576 Polymorphism with Sociality: A Meta-Analysis

Abstract: A common variant in the oxytocin receptor gene (OXTR), rs53576, has been broadly linked to socially related personality traits and behaviors. However, the pattern of published results is inconsistent. Here, we performed a meta-analysis to comprehensively evaluate the association. The literature was searched for relevant studies and effect sizes between individuals homozygous for the G allele (GG) and individuals with A allele carriers (AA/AG). Specifically, two indices of sociality were evaluated independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
130
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(142 citation statements)
references
References 57 publications
8
130
1
3
Order By: Relevance
“…What little work has been done suggests that variation in OXTR can predict the size and diversity of social networks via its influence on social temperament (45), as well as being related to feelings of social connectedness (46) and "general sociality" (47). Other studies have, however, provided indirect evidence for a relationship between endorphins and social network size (48).…”
mentioning
confidence: 99%
“…What little work has been done suggests that variation in OXTR can predict the size and diversity of social networks via its influence on social temperament (45), as well as being related to feelings of social connectedness (46) and "general sociality" (47). Other studies have, however, provided indirect evidence for a relationship between endorphins and social network size (48).…”
mentioning
confidence: 99%
“…We know of two reported replication failures of OXTR gene effects (Apicella et al, 2010; Munk, Hermann, El Shazly, Grant, & Hennig, 2016). Furthermore, two recent meta-analyses reported equivocal results regarding the influence of two heavily studied human OXTR SNVs on sociality, with (Bakermans-Kranenburg & van Ijzendoorn, 2014; Li et al, 2015). Similarly, though several studies have implicated a 5′ AVPR1A polymorphism in chimpanzee social behavior, the identified effects have been inconsistent.…”
Section: | Discussionmentioning
confidence: 99%
“…In particular, associations have been found between the genetic variation of different genes involved in the oxytocinergic system and a variety of social phenotypes in different mammalian species, e.g., mice (see Caldwell et al, 2016 for a review), primates (Staes et al, 2014), cats (Arahori et al, 2015), humans (see Ebstein et al, 2012 for a review), and dogs (Kis et al, 2014). For example, polymorphisms in the oxytocin receptor ( OXTR ) gene were associated with dogs’ proximity seeking with the owner (Kis et al, 2014), rough temperament in cats (Arahori et al, 2015), and sociability in humans (Li et al, 2015). Furthermore, oxytocin has been associated with social fear (Kirsch et al, 2005), aggression toward unfamiliar individuals (Stallen et al, 2012) and social anxiety (Grillon et al, 2013) in humans, and friendliness toward a threatening human in dogs (Hernádi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%